Interactive learning package for artificial neural network (Demonstration Module) / Camellia Mohd Kamal - Camellia , Mohd Kamal (2004)
Interactive Learning Package for Artificial Neural Network (Demonstration Module) is a learning package that allow the users to learn and enhance the understanding of the ANN subject in more detailed way and apply in the demonstration parts. Every demonstration will be followed by a brief and compact explanation therefore the user can understand more clearly about the demonstration and know hoe to do it very well. The demonstration module provides the users only with the important notes that the user must know because the explanation already described in learning modules. For the tutorial questions, for the demonstration modules most of the question are the calculation format based on the demonstration example. Every question is related because from there we can know the levek of the user. Five main topics will be discussed in this learning Package, which are the Introduction of Artificial Neural Network, Perceptron, Feed Forward, Recurrent Network and Self Organizing Maps (SOM). The introduction topic will discuss about the biological neuron with one demo, directed graph description also with one demo, the neuron model that included three subtopic; single input neuron with one demo, directed graph description also with one demo, architecture of all the network layers with two subtopics Layer of neuron and multiplayer neuron. For Perception there will be the Description Neuron Model, Perceptron Basic Architecture and perceptron Algorithm with one example of solved problem. For the Feed Forward, Recurrent and Self Organizing Map Networks there are the Neuron Model, Basic Architecture and Training Algorithm. The demonstrations are included each every topic. It also has glossary that gives sense to certain new words in the next. In providing convenience to users, this system is developed as a stand-alone application. The system is built-up in convergence of artificial neural network concepts and the latest available Macromedia Flash MX and it runs on the requirement of Windows 98 and above operating system. This system will describe the demonstration mechanism that is controlled by the hypermedia elements and that attempts to assist the student to learn the material and concepts presented with their participation.